The contemporary intelectual crisis and lack of clear perception of science and scientific thinking - Ali, Muhammad Mumtaz; Chisthti, Siddiq Ali (International Islamic University Malaysia, 2015)
It seems that the contemporary world, Western and Eastern, is suffering from and acute intellectual crisis and lack of clear perception of science and scientific thinking.This is visible everywhere in the current empirical realities in political, economic, technological, social and educational domains of life.It is, therefore, conducted here that there is an urgent need to revisit the so-called metaphysical paradigm of modern Western science and scientific thinking. It is argued the crisis has been caused owing to, on one side, the refusal of the modern world to accept the existence of True, Authentic and Universal Knowledge[the Islamic revelation]and Truth and Reality of Life and the World as expounded by Islamic revelation. It is maintained here that the dominant modern Western metaphysical paradigm of thinking, thought and action is based on speculation and conjecture instead of True, Authentic and Universal Knowledge. The Qur'an, in fact, challenges mankind and ask them to adopt the framework of scientific thinking; it initiatives people to thinking properly and follow the right method of scientific thinking. The main goal of this paper is to provide an exposition of the meaning of true scientific thinking and its method.